Rights, not rescue: trafficking (in)securities at the sport mega-event - Oliver, Benton J.; De Lisio, Amanda (Frontiers in Sports and Active Living, 2023)
We examine the impact of fantasies used in the redevelopment of sport mega-event cities on host communities; particularly as related to the male-dominated FIFA World Cup and forced prostitution. We start with a discussion of event fantasies, particularly those that circulate in relation to humanitarian aid and the alleged involvement of women and children in forced labour and sexual exploitation. We trace these fantasies across several FIFA host cities since the 2006 FIFA World Cup, hosted in Germany, to leverage continual and perpetuate attention (and profit) through the non-profit industrial complex. These fantasies have facilitated and coordinated collaborative consensus amongst state authorities and allies to act in a meaningful manner even as the evidence of forced prostitution is still scant—while the realities of people that continue to be subjected to violent and exploitative labour in the construction of stadia, athlete recruitment, or equipment and apparel industries are seldom addressed. We do this to question the lived impact of policies and personalities of rescue on people engaged, consensually, in erotic labour within host cities, that are often made target of rescue intervention. The figure of the proverbial sex slave, as a highly racialized and hypersexualized trope, is mobilized through the sport mega-event to further police the bodies of all women in labour and migration. We end with a cautious message to future host cities, particularly cities implicated in the 2026 FIFA World Cup within Mexico, Canada, and the United States, of the highly-profitable and politically-advantageous rhetoric of damsel in distress.